Knowledge Linkage: A Social Network Analysis of Tourism Dissertation Subjects - Ying, Tianyu; Xiao, Honggen (Journal of hospitality & tourism research (Washington, D.C.), 2012)
Research subjects are indicative of problem areas amongst which knowledge traffic occurs and networks form in a scientific community. This article presents a social network analysis of tourism dissertation subjects based on ProQuest Dissertations and Theses–Full Text database (1994-2008). The study suggests an openness and vibrancy of tourism as a domain of knowledge from a social network perspective. Longitudinal examinations revealed a structural change in its knowledge development. Twenty-one subjects were identified as subdomains in this dynamic and interconnected knowledge system. The article also discusses the relationships between subject areas and doctoral program distributions for tourism research at North American institutions. Results of the study contribute to discussions on scientific community and knowledge networks in interdisciplinary tourism studies.